2022
DOI: 10.1038/s41598-022-22552-y
|View full text |Cite
|
Sign up to set email alerts
|

Diminished neutralization responses towards SARS-CoV-2 Omicron VoC after mRNA or vector-based COVID-19 vaccinations

Abstract: SARS-CoV-2 variants accumulating immune escape mutations provide a significant risk to vaccine-induced protection against infection. The novel variant of concern (VoC) Omicron BA.1 and its sub-lineages have the largest number of amino acid alterations in its Spike protein to date. Thus, they may efficiently escape recognition by neutralizing antibodies, allowing breakthrough infections in convalescent and vaccinated individuals in particular in those who have only received a primary immunization scheme. We ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…We next assessed the neutralizing activity of Clec9A-RBD immune sera against a panel of 20 sarbecoviruses, which includes SARS-CoV-2 variants of concern (VOCs), SARS-CoV, and animal CoV from the bat and pangolin lineages [25]. The neutralizing activity against most SARS-CoV-2 VOCs increased over time and persisted throughout the 21-month monitoring period (Figure 2A and S2A), except for Omicron lineages, which was not surprising given the extended repertoire of immune escape mutations and in line with previous reports [26]. Interestingly, neutralizing activity against clade-1B sarbecoviruses from bat and pangolin species (RaTG13, BANAL-52, BANAL-236, GD-1, Gx-P5L) was readily detected at all the time points tested, that increased progressively throughout the 21-month monitoring period (Figures 2A and S2A).…”
Section: Sars-cov-2 Variants and Sarbecovirusessupporting
confidence: 86%
“…We next assessed the neutralizing activity of Clec9A-RBD immune sera against a panel of 20 sarbecoviruses, which includes SARS-CoV-2 variants of concern (VOCs), SARS-CoV, and animal CoV from the bat and pangolin lineages [25]. The neutralizing activity against most SARS-CoV-2 VOCs increased over time and persisted throughout the 21-month monitoring period (Figure 2A and S2A), except for Omicron lineages, which was not surprising given the extended repertoire of immune escape mutations and in line with previous reports [26]. Interestingly, neutralizing activity against clade-1B sarbecoviruses from bat and pangolin species (RaTG13, BANAL-52, BANAL-236, GD-1, Gx-P5L) was readily detected at all the time points tested, that increased progressively throughout the 21-month monitoring period (Figures 2A and S2A).…”
Section: Sars-cov-2 Variants and Sarbecovirusessupporting
confidence: 86%
“…Multiple studies have clearly shown that there is significant reduction in neutralization by vaccine-induced antibodies against the Omicron variant of concern, compared to the ancestral SARS-CoV-2 strain as well as prior variants of concern (i.e., Alpha, Delta). [14] , [15] , [16] , [17] Differences in neutralization among Omicron BA subvariants, however, are minimal. A recent review of 178 studies that summarized post-vaccination neutralization against multiple Omicron subvariants showed that in general BA.2 subvariants had similar neutralization capacity after primary series and booster dose vaccination compared to BA.1, for all vaccines tested (i.e., mRNA, vector-based, inactivated, protein subunit); the relative fold reduction in neutralization of BA.2 compared to BA.1 was 0.9 [Inter-quartile range (IQR) 0.7-1.2].…”
Section: Neutralization By Omicron Subvariantmentioning
confidence: 95%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the coronavirus disease 2019 (COVID-19) pandemic, continues to circulate across the globe while rapidly evolving. The beginning of 2022 was marked by the emergence of Omicron BA.1/BA1.1 variant, establishing a turning point in the pandemic with decreased pathogenicity [1][2][3][4][5] , increased transmissibility 2 , and enhanced immune escape [6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%